El verbo y las partes invariables de la oración en el Dictamen de la comisión de gramática (1861) de la Real Academia Española - Hernando García-cervigón, Alberto (Revista de Filología Románica, 2006)
The main objective of this paper is the analysis of the grammatical doctrine of the verb and the invariable parts of the speech contained in the Dictamen de la Comisión de Gramática (1861), project of reform precedent to the edition of 1870 of the GRAE with the aim of determining the possible influences received and its consequences in that edition of the GRAE. Therefore, we have examined in detail not only the text corresponding to that report, developed for the internal use of the different members of the Corporation but also all the editions of the Gramática and the Minutes and unpublished Grammar Documents which are kept up in the Archives of the RAE where is possible to find very important data to ascertain its evolution in that specific context of grammatical tradition.